(untitled) (Modern information system and technologies, 2018)
The purpose of this study is to examine configurations of quasi-fractal 3D-antennas, which are based on using a truncated cone as the basic element. As part of the research, the directivity patterns and the amplitude frequency responses were investigated, as well as their dependence on mutual arrangement of the elements. This paper provides the results of antenna simulations performed with Ansys HFSS.